Effects of post-adoption beliefs on customers' online product recommendation continuous usage: An extended expectation-confirmation model - Muhammad Ashraf; Jamil Ahmad; Asad Afzal Hamyon; Muhammad Ramzan Sheikh; Wareesa Sharif (Cogent Business & Management, 2020)
This study aims to extend expectation-confirmation model (ECM) of IS continuance based on effort-accuracy model (EAM) for predicting and explaining continuous usage of online product recommendation (OPR) that has been ignored in prior literature. The proposed OPR continuance model, incorporating the post-adoption beliefs of perceived usefulness, perceived decision quality and perceived decision effort, was empirically validated with data collected from an online survey of 626 existing users of the OPR. Results indicated a good explanatory power of the OPR continuance model (R2 = 62.1% of OPR continuance intention, R2 = 53% of satisfaction, R2 = 50.5% of perceived usefulness, and R2 = 9% of perceived decision effort, and R2 = 72.3% of perceived decision quality), with all major paths supported except one. We also analysed the data on the original ECM that reveals lower variances explained compared to the OPR continuance model (D6% in OPR continuance intention, D5.1% in customer satisfaction, and D3.2% in perceived usefulness). The salient effect of perceived decision quality signifies that the nature of the IS can be an important boundary condition in understanding the continuance behaviour. At a practical level, this study presents deeper insights into how to address users' satisfaction and continued patronage.
Keywords: 650; online product recommendation; decision effort; decision quality; usefulness; satisfaction; OPR continuance intention